Virtual and Imaginative Mobility: How Do We Bring the Outside Indoors and What Happens When Mobility is no Longer Available? - Charles Musselwhite (Transport, Travel and Later Life, 2017)
There is clear and robust evidence of the importance of going outdoors to the health and wellbeing of older people. However, modern technologies have enabled more and more of the outside world to be brought inside. Though, it can be hypothesised that this is a poor substitute for literally being outdoors, little is understood as to why this is, not how much of the outdoors could be re-presented indoors to give benefits. This chapter briefly gives examples of how new technologies can bring the outdoors inside and potential advantages of doing that to help older people stay connected to other people and the outside world. It highlights what is still missing from literally engaging with the outdoor world, for example the social connection with other people, random-chance encounters with others, over reliance on visual representation and a lack of control. The absence of the mundane in many of the re-presentations of the outdoor world is also evident and this appears to be important in literal interactions with the outside world. Nevertheless, there appears to be great promise in connecting people to the outside world without literally having to go outdoors, especially for those with mobility impairments who are unable to get out and about.